TYPICAL MISTAKES OF STUDENTS IN MATHEMATICS AND SOME WAYS TO OVERCOME THEM (Scientific journal of the Fergana State University, 2023)
In this article, typical student errors were investigated in solving the tasks of stereometry and the ways to overcome them.